Determination of Stature from Anthropometric Measurements of Thyroid Cartilage in the Population of Punjab - Sunil Subramanyam1, Dalbir Singh2, YS bansal3, SP Mandal4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The astonishing task of determining the identity of an individual has been simplified, with the innovation of scientific technologies like DNA fingerprinting in the developed countries. Yet the application of such advanced technologies in developing countries is still a daunting task due to its complexity. Anthropometric analysis for the identification of unknown bodies is reasonably productive owing to its inexpensiveness. The aim of this study was to correlate the anthropometric measurements of the thyroid cartilage with the stature of the individual. Thyroid cartilages from 300 post mortem cases done in native population of Punjab were studied anthropometrically. A total of seventeen anthropometric measurements of selected parameters of thyroid cartilage were defined, measured, and statistically correlated with the body length of the individual. The variables which were significantly correlating with the body length were further analysed by regression analysis for derivation of a regression equation.